1990
DOI: 10.1063/1.103277
|View full text |Cite
|
Sign up to set email alerts
|

Integrated optic adiabatic polarization splitter on silicon

Abstract: An adiabatic polarization splitter, fabricated with silica and silicon nitride films on a silicon substrate, is demonstrated. A rejection of the unwanted polarization (cross talk) of −20 to −34 dB was achieved with single filtering and −35 to −45 dB with double filtering. The device had a 1.5 dB insertion loss and a very small wavelength dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…In contrast to the long device length of the conventional branch-type splitter (> 1000 µm) [8]- [11], the present splitter is found to have a noticeably short device length of less than 200 µm. Fig.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…In contrast to the long device length of the conventional branch-type splitter (> 1000 µm) [8]- [11], the present splitter is found to have a noticeably short device length of less than 200 µm. Fig.…”
Section: Introductionmentioning
confidence: 65%
“…It is observed that the fields of the two waves are successfully separated into the Waveguides #1 and #2 around z = 200 µm. The device length is found to be remarkably shorter than that of the conventional branch-type splitter [8]- [11]. …”
Section: B Reduction In the Tm-wave Field In Waveguide #1mentioning
confidence: 94%
See 2 more Smart Citations
“…All variants of integrated optics based polarization splitters rely on the waveguide birefringence phenomenon [69]. There are different implementations of the splitter in the literature such as; birefringent directional couplers [70,71], asymmetric Y junctions [72][73][74], interference based birefringent splitters [75,76], grating based devices [77][78][79] and photonic crystal based devices [80].…”
Section: Integrated Optics Polarization Splittermentioning
confidence: 99%